Pemberdayaan Masyarakat Pelaku UMKM Melalui Pelatihan Penyusunan Proposal Usaha dan Analisis Laporan Keuangan di Kabupaten Kampar - Puspita Sari, Anisa; Alfinasari, Safitri; Puspito Rahayu, Tri; Purnama Putri, Intan; Novita Sari, Tri; Kusuma Hadi Soedjoko, Dodi (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Micro Small and Medium Enterprises (MSMEs) play an important role in Indonesia. MSMEs have shown their tenacity and resilience in the economic crisis and along with the Covid-19 pandemic, it is hoped that MSMEs will survive again. Especially among MSME actors in Kampar Riau Regency with fields that are engaged in culinary, agriculture, fisheries, and handicrafts. This group was chosen because of the high number of MSMEs in Kampar Regency (45,446 MSMEs) and the abundant natural resources (HR) potential in the area. The aim behind this activity is to equip MSMEs with the autonomous capacity to plan strategic deals and dissect financial reports so that they can be used as a reference to turn them into a company so that they can turn into individual financial strengths and make major commitments to national finance. This activity is carried out through direct contact with a limited number of MSMEs. This strategy was taken in view of the outbreak of the corona virus pandemic. The stages of this activity begin with clarification of the obstacles that are often faced by MSMEs, followed by clarification of the importance of strategic agreements, the efforts taken in preparing strategic plans, and the importance of auditing budget reports. These results have expanded the capacity and information of MSMEs, especially in Kampar Regency in terms of strategic agreement planning and monetary reports, even in limited circumstances due to the Coronavirus pandemic.